1968
DOI: 10.1111/j.1532-5415.1968.tb02684.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial L‐forms From Urinary‐tract Infections in a Veterans Hospital Population*

Abstract: In a study of 115 patients with chronic and acute urinary‐tract infections, 26 (23 per cent) were found to have bacterial L‐forms in the urine which could be cultured in a special hypertonic medium. The most common genera of bacteria producing these forms were Proteus, Pseudomonas and Escherichia‐Aerobacter. Most of the patients had cystitis, pyelonephritis or a general diagnosis of “urinary‐tract infection.” In a case of acute exacerbation of chronic pyelonephritis, the L‐form of Proteus mirabilis appeared af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1969
1969
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The perpetuation of cystitis despite antibiotic treatment of these elderly surgical patients may be related to several factors (Table 2). Bacteria may persist within the urinary tract as L‐forms or protoplasts, with possible reversion to a pathogenic organism when antibiotic therapy is withdrawn (9,10). However, the importance of protoplast formation in recurrent human cystitis is uncertain and incompletely documented.…”
Section: Discussionmentioning
confidence: 99%
“…The perpetuation of cystitis despite antibiotic treatment of these elderly surgical patients may be related to several factors (Table 2). Bacteria may persist within the urinary tract as L‐forms or protoplasts, with possible reversion to a pathogenic organism when antibiotic therapy is withdrawn (9,10). However, the importance of protoplast formation in recurrent human cystitis is uncertain and incompletely documented.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, L-form antigens could not be developed. The role of transitional forms and L-forms of organisms in disease is not well defined, but there is evidence that this type of growth may be important in latent or recurrent infections, as in septicaemia (Wittler, Malizia, Kramer, Tuckett, Pritchard, and Baker, 1960;Mattman and Mattman, 1965), subacute bacterial endocarditis (Rosner, 1966;Zierdt and Wertlake, 1969), and urinary tract infections (Gutman and others, 1965;Conner, Coleman, Davis, and McGaughey, 1968). The isolation of the L-form of a diphtheroid-like bacteria in a very high percentage of blood cultures from rheumatoid patients has been described (Pease, 1969(Pease, , 1970.…”
Section: Antibody Studiesmentioning
confidence: 99%
“…Some authors have found L-phase organisms in 20 per cent. of patients with suspected urinary-tract infections (Gutman et al, 1965;Conner et al, 1968). This might be due to the favourable conditions for survival of L-phase organisms within the urinary tract because kidney tissue and urine are very hypertonic compared with other organs and body fluids.…”
Section: T R E a T M E N T O F Experimental L-phase I N F E C T I O Nmentioning
confidence: 99%